Constraining development : the shrinking of policy space in the international trade regime - Thrasher, Rachel (London : Anthem Press, 2021)
There is a fundamental mismatch between the global trade rules as they govern international economic behaviour and the political economic factors influencing domestic policy making. It comes as no surprise, therefore, that the multilateral trading system is in crisis. Countries are increasingly turning to bilateral and regional (and mega-regional) trade deals to push forward their trade agenda. There is far less consensus around these next-generation trade agreements which reach into every aspect of domestic policy-making. At this time, more than ever, policy-makers, treaty negotiators, and scholars and students of international law need to understand the ways in which this growing regime of international trade and investment impacts regulatory decisions. This book demonstrates how seemingly disparate spheres of legal theory and practice (investment incentives, patent protection, land reform, etc.) are all linked together through the lens of international trade and investment, while also offering solutions in the form of new negotiating texts and country examples as a way forward toward a new multilateral trade and investment regime. Furthermore, each chapter identifies the regulatory challenges facing countries.
1. Constraining Policy Space: How Global Trade Rules Conflict with National Development Goals -- 2. Modern Trade Agreements, Industrial Policy and Development Sovereignty -- 3. Trade-Related Aspects of Intellectual Property, Investment Rules and Access to Medicines -- 4. Land Grabs, Land Governance and International Investment Commitments -- 5. Capital Flow Regulation and Trade Agreements: An Empirical Investigation -- 6. The Emerging Role of International Investment Agreements in Sovereign Debt Restructuring -- 7. Trade and Investment Policy for Climate Change and the Energy Transition -- 8. Conclusion: A Way Forward.
Title from publisher's bibliographic system (viewed on 23 Feb 2022).
Keywords: Foreign trade regulation; Policy sciences; International relations; Treaties